(untitled) (Pulse, 2016)
Introduction: Extended spectrum ?-lactamases (ESBLs) are enzymes that mediate resistance to extended-spectrum (third generation) cephalosporins (e.g., ceftazidime, cefotaxime, and ceftriaxone) and monobactams (e.g., aztreonam) but do not affect cephamycins (e.g., cefoxitin and cefotetan) or carbapenems (e.g., meropenem or imipenem). Though the no. of ESBLs producing organism has been increasing day by day, the detection methods and treatment option for them are extremely limited. Aims & Objective: The present study was undertaken to investigate the rate of ESBLs production and their antibiotic susceptibility pattern. Materials & Method: A total 110 Gram negative isolates from various clinical samples from a tertiary care hospital were studied and ESBLs production was detected by double disc synergy test. Antibiotic susceptibility test was done for commonly used antibiotics. Results: Among the total isolates 66.36% (73) were ESBLs producer, and the rate of ESBLs positivity was 80.32% for E.coli (49 out of 61), 25% for Pseudomonas spp (6 out of 24), 71.42% for Klebsiella spp (10 out of 14), 80% for Enterobacter spp (4 out of 5), 100% for Acinetobacter spp (4 out of 4) and 0% for Proteus spp (0 out of 2). ESBLs producing organisms were resistant to most of the antibiotics but 100% were sensitive to imepenem. Conclusion: Screening for ESBLs production needs to be carried out routinely in every clinical diagnostic laboratory to guide clinicians in proper selection of antibiotics. Pulse Vol.8 January-December 2015 p.15-20